Modelo de madurez de Data Governance - Alfaro Carranza, Rosa Ángela (2015)
Data Governance is a concept in evolution which includes people who have large responsibilities within organizations and the processes that these used to be able to manage information. This project proposes the creation of a maturity model of data governance based on the IBM Data Governance Maturity Model. The objective of this model is to help organizations to understand their level of maturity in relation to the management of your data and identify its weaknesses to subsequently take corrective action before opting for the implementation of a Data Governance program.